2018
DOI: 10.2139/ssrn.3238544
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Activation and Youth Crime

Abstract: We evaluate the impact on youth crime of a welfare reform that tightened activation requirements for social assistance clients. The evaluation strategy exploits administrative individual data in combination with geographically differentiated implementation of the reform. We find that the reform reduced crime among teenage boys from economically disadvantaged families. Stronger reform effects on weekday versus weekend crime, reduced school dropout, and favorable long-run outcomes in terms of crime and education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…The results are shown in column (3) of Table 8. The effects of reducing the destruction rates are similar to those from the previous simulation, generating a large increase in total employment (15.6%-points), a 50 Job search assistance programs and job placement programs are examples of policies that can reduce frictions in the legal labor sector, particularly for individuals with a criminal background (Uggen, 2000;Wilson et al, 2000;Bratsberg et al, 2019).…”
Section: Counterfactualssupporting
confidence: 55%
“…The results are shown in column (3) of Table 8. The effects of reducing the destruction rates are similar to those from the previous simulation, generating a large increase in total employment (15.6%-points), a 50 Job search assistance programs and job placement programs are examples of policies that can reduce frictions in the legal labor sector, particularly for individuals with a criminal background (Uggen, 2000;Wilson et al, 2000;Bratsberg et al, 2019).…”
Section: Counterfactualssupporting
confidence: 55%
“…To the best of our knowledge,Miller and Saunders (1997) are the first to examine the effect of welfare generosity on educational attainment. They did not find any significant impact on high school completion, but one may question whether the between-states comparison of this early study provides convincing causal evidence.6 The stricter activation requirements were implemented by local authorities and covered community service, participation in work or training programs, general work counseling, and active job search Bratsberg et al (2019). build on the paper ofHernaes et al (2017) to demonstrate that these stricter activation requirements also reduced crime among teenage boys from disadvantaged families, partly arising "from the simple fact that when youth are kept occupied by activation or in school, there is less time and opportunity left for committing crime" (p. 561).…”
mentioning
confidence: 81%
“…Dahlberg et al (2009), looking at the gradual implementation of mandatory activation programs in Stockholm city districts, found reduced welfare participation and increased employment. Similarly, Hernaes et al (2017), Bratsberg et al (2019) and Hernaes (2020) looked at the gradual introduction of conditionality for welfare recipients in Norway during the late 1990s and early 2000s and found that it led to a lower share of youths receiving welfare benefits, less crime and higher high school completion rate and earnings. But not all studies find that activation policies have positive effects.…”
mentioning
confidence: 99%